Factors affecting hotel employees' performance / Rosliza Md Zani, Farah Merican Isahak Merican and Nur Sara Elenna Mazlan - Md Zani, Rosliza; Isahak Merican, Farah Merican; Mazlan, Nur Sara Elenna (Universiti Teknologi MARA, Perlis, 2018)
Employee performance is defined as whether a person executes their job duties and responsibilities well since performance is a critical factor in organizational success. For that purpose, it requires the understanding for a particular position and that the employee knows the job performance basics and measures that he or she is relied upon to meet. This research aims to study the relationship between performance predictors such as empowerment, teamwork, and work environment with employee performance in hotel industry. It was found that teamwork and work environment have significant correlation with employees' performance. This research concluded that there is a strong relationship between teamwork and employees' performance, and also is the most dominant factor that influences employee performance.